The Influence Of Motivation And Work Discipline On The Performance Of Kahuripan Puskesmas Employees Tasikmalaya City - Valenza, Ryan Febian; Rahwana, Kusuma Agdhi; Karmila, Mila (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
This research aims to determine the influence of work motivation and discipline on employees of the Kahuripan Tasikmalaya City Health Center. The method used was quantitative with a research sample of 38 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS. Based on the results of this research, it shows that Work Motivation and Discipline simultaneously have a positive and significant effect on Employee Performance. Motivation partially has a significant effect on employee performance. Work Discipline partially has a significant effect on Employee Performance.